The UCSF Faculty Development Workshop on Critical Reflection in Medical Education: Training Educators to Teach and Provide Feedback on Learners' Reflections - Louise Aronson; Marieke Kruidering; Patricia S. O'Sullivan (Association of American Medical Colleges, 2012)
Abstract This guide describes a literature-derived workshop to train faculty in the skill of critical reflection and to teach them to foster the skill in their learners. The basic workshop lasts two hours, and we provide options for two different three hour workshops and one four hour long workshop as well. All versions of the workshop encourage participant interaction throughout through the use of multiple teaching modalities: individual, small and large group exercises; use of written materials, white board/flip charts and PowerPoint. Participants apply their skill as educators to analyze more and less effective reflections, are introduced to the concepts and data surrounding critical reflection in medical education and a structured approach for promoting effective and educational reflection, practice giving feedback on critical reflections. In the longer workshops, they may also write critical reflections themselves, gain additional feedback experience, and draft approaches to incorporating reflection in the courses and curricula to assess competencies. Materials include: a PowerPoint slide set; two sets of sample reflections (5 total), each with an annotated presenter's guide; a sheet for rating and evaluating sample reflection quality; the UCSF LEaP Guide, a structured approach to critical reflection; guidelines for providing feedback on both content and reflective skill of critical reflections; a prompt for faculty critical reflection; and a workshop evaluation form. As of August 2011, the authors had given this workshop 19 times, receiving consistently high ratings (mean overall rating 4.6 on a 5 point scale), moderately high rates of self-efficacy (4.2 out of 5), and leading to substantial implementation of critical reflection by trained faculty (74%) and broad dissemination locally and at other institutions across the United States. At UCSF, the impact of the workshop has included greater teaching of critical reflection throughout the medical curriculum (e.g. in pre-clerkship lab exercises for first year medical students, in many core clerkships, and in the medical student portfolios for competency milestone assessment; in residencies from Emergency Medicine to Psychiatry and in several fellowships), greater consistency in using reflection and critical reflection accurately and appropriately, coordination of reflective skills training across courses and clerkships, and more consistent feedback to learners on their reflective exercises. Participants from other institutions, including Stanford, the University of Colorado, FSU, Hofstra, and the University of Toronto, who took the workshop at regional and national meetings have contacted us and indicated that they have adopted our approach to critical reflection. Importantly, while there have been brief reports about faculty training in reflection, we have not found other workshops based on the literature and extensive medical education experience which have been thoroughly described, broadly disseminated, and evaluated across learner levels and institutions (paper in progress) as this one has.